Flatness-based linear active disturbance rejection control for tower crane - Sev Eunet Rs; Tuan Anh Nguyen; Minh Duc Duong (FME Transactions)
Controlling tower cranes presents substantial challenges due to their complexity, nonlinearity, and under-actuated dynamics. This paper introduces a control strategy integrating Linear Active Disturbance Rejection Control (LADRC) with differential flatness theory to achieve precise trolley positioning and effective swing elimination. To simplify the system model, we apply differential flatness theory to define the system output, allowing us to treat uncertainties and external disturbances as a singular total disturbance. The control methodology is grounded in LADRC principles. Additionally, we employ Simulated Annealing-Particle Swarm Optimization (PSO-SA) to fine-tune the controller parameters. The simulation results demonstrate that the proposed control method exhibits robust performance against uncertainties.